Myanmar (Burma) (United Kingdom : APA Publishing, 2015)
With its glittering pagodas, timeless countryside and gracious people, Myanmar (Burma) is an extraordinarily beautiful destination, but one that was isolated from the rest of the world until very recently. With tourism growing rapidly and ongoing development as the country opens up, there has never been a better time to explore Myanmar. Following on from our best-selling, award-nominated re-launch in 2013, the 2015 Insight Guide Myanmar (Burma) has been comprehensively updated by an expert author to help inspire and inform travellers wanting to discover this fascinating country. After an inspirational best Of Myanmar section, the country's rich past and cultural heritage are described in a series of lively essays. Contemporary aspects of Burmese life - the changing political situation, the economy, food, architecture, wildlife - are also covered in depth. The places chapters describe all the sights that should be seen - from the incomparable temples of Bagan, serene Inle Lake, the lost world of Mrauk U and the beaches along the Bay of Bengal to the fascinating cities of Yangon and Mandalay. Detailed, high-quality maps throughout will help you get around and travel tips give you all the essential information for planning a memorable trip, including our independent selection of the best hotels and restaurants. Discover this most exciting of destinations with Insight Guide Myanmar (Burma).
Includes index
Primary
Keywords: Burma; Burma -- Guidebooks